2017
DOI: 10.1093/cid/cix494
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rotavirus Vaccine Introduction and Postintroduction Etiology of Diarrhea Requiring Hospital Admission in Haydom, Tanzania, a Rural African Setting

Abstract: SummaryWe describe the substantial impact of rotavirus vaccine introduction on all-cause and rotavirus diarrhea admissions to a rural Tanzanian referral hospital. Despite this impact, rotavirus remained the leading etiology of diarrhea requiring hospitalization in the third year after vaccine introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 45 publications
9
33
2
Order By: Relevance
“…The high norovirus prevalence corresponds well with other studies in high-and middle-income countries where norovirus has become the most common aetiology in severe childhood diarrhoea [12][13][14]. Other studies from Malawi and Tanzania have shown lower prevalence of norovirus compared to this study, but used other detection methods that might not be directly comparable [27,28]. Most of the rotavirus positive children (55%) in this study were symptomatically infected despite having received a full three-dose regimen of rotavirus vaccine, indicating a less than optimal protective effect of the vaccine.…”
Section: Discussionsupporting
confidence: 83%
“…The high norovirus prevalence corresponds well with other studies in high-and middle-income countries where norovirus has become the most common aetiology in severe childhood diarrhoea [12][13][14]. Other studies from Malawi and Tanzania have shown lower prevalence of norovirus compared to this study, but used other detection methods that might not be directly comparable [27,28]. Most of the rotavirus positive children (55%) in this study were symptomatically infected despite having received a full three-dose regimen of rotavirus vaccine, indicating a less than optimal protective effect of the vaccine.…”
Section: Discussionsupporting
confidence: 83%
“…While some reports have associated DAEC with diarrhea [11,33,34], another ones have appointed for similar proportions of DAEC in case and controls [9] in alignment with our findings. In contrast with our findings, recent studies conducted in sub-Saharan Africa associated EIEC to diarrhea [35,36]. At least, the lower circulation of EHEC is not surprisingly, since previous studies conducted in Mozambique revealed low circulation of this pathotype in Manhiça [5] and absence in Maputo city [11,14,15].…”
Section: Discussioncontrasting
confidence: 99%
“…Similar findings were observed in Tanga, where the prevalence of RVA declined from 29-41% [20,37] to 10-29% [37]. These results are complemented by other similar case control studies conducted in the post-vaccination era, which found a 44.9% reduction in rotavirus hospitalization in Manyara in 2015 [47] and reductions of 40%, 46%, and 69% in Zanzibar in 2013, 2014, and 2015, respectively [33]. The progressive reduction in rotavirus hospitalizations in Zanzibar, Mbeya, Dodoma and Moshi could be attributed to the increasing coverage of the rotavirus vaccine.…”
Section: Trends Of Rotavirus Infection and Impact Of The Rotavirus Vasupporting
confidence: 85%
“…Similar findings in the delay of the seasonal peak after vaccine introduction have been reported in the United States [52]. Before vaccine introduction, the peak months were May 2009 and August 2011 in Tanga, May 2012 in Mwanza, May-July of 2010-2012 in Manyara and July 2010 and May of 2011-2012 in Zanzibar [33,37,47]. After vaccine introduction, the peaks in rotavirus cases were delayed for 1-4 months towards the end of the year; in Tanga, the peak was in September of 2014-2015; in Mwanza, it was in July 2014 and July and August of 2015; in Manyara, it was in August-October of 2013-2015 and in Zanzibar, it was in June and July of 2013, September 2014 and October 2015 [33,37].…”
Section: Trends Of Rotavirus Infection and Impact Of The Rotavirus Vasupporting
confidence: 79%